Interação de uma díade mãe-criança cega no contexto de alimentação - Gandolfine, Milena (Universidade Federal de São Carlos, 2017)
Among the various situations in human life that constitute social interactions, those between the sighted mother and her visually impaired child, stand out for their importance for the child's development. The aim of this study was to characterize the sighted mother - blind child interaction classes defined/named as “Gain” or “Loss” of educational opportunities by the mother for her visually impaired child, in the context of child feeding. The participants were a congenital blindness child and her sighted mother. The sighted mother-blind child interactions were video-recorded by the mother during the child's feeding, in the dyad's residence. For the analysis of the dyad's performance, treatment protocols and data analysis for children with and without visual impairment were used. In relation to the mother's behavior, the results indicated a greater number of occurrences of opportunities for gain, signaling the seizing by the mother of the possibilities to promote the child's development. In relation to the performance of the dyad, there was a greater number of occurrences of loss. The last result requires additional analysis and discussion on the development of an appropriate analysis instrument for the examination of the conditions of development of the population of children with visual impairment.
Mother-blind child dyad interaction in feeding context
Keywords: Interação mãe-criança; Deficiência visual; Desenvolvimento infantil; Mother-child interaction; Visual impairment; Child development; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM